Scavenger Receptor B2 as a Receptor for Hand, Foot, and Mouth Disease and Severe Neurological Diseases - Yamayoshi, Seiya; Fujii, Ken; Koike, Satoshi (Frontiers in Microbiology, 2012)
Enterovirus 71 (EV71) is one of the major causative agents of hand, foot and mouth disease (HFMD). Infection with EV71 is occasionally associated with severe neurological diseases such as acute encephalitis, acute flaccid paralysis and cardiopulmonary failure. Because cellular receptors for viruses play an important role in cell, tissue and species tropism, it is important to identify and characterize the receptor molecule. Recently, cellular receptors and host factors that stimulate EV71 infection have been identified. Several lines of evidence suggest that scavenger receptor class B, member 2 (SCARB2) plays critical roles in efficient EV71 infection and the development of disease in humans. In this review, we will summarize the findings of recent studies on EV71 infection and on the roles of SCARB2.